STRATEGI PENGEMBANGAN POTENSI PARIWISATA DI PANTAI DUTA KABUPATEN PROBOLINGGO - Choridotul Bahiyah; Wahyu Hidayat Riyanto; Sudarti Sudarti (Program Studi Ekonomi Pembangunan, 2018)
Tourism development in a region brought benefits to community either economically, social, and culture. Probolinggo Regency has various tourism objects. One of them is Duta beach. It needs correct strategy to pull tourists interest to visit Duta beach tourism object. This research is descriptive qualitative which review Duta beach tourism potential development strategy in Probolinggo regency based on internal and external factors. Population in this research are visitors in Duta beach tourism object by using SWOT analysis. Research shows that internal and external factors influenced tourists visits in Duta beach tourism objects. SWOT analysis is strategy of planning and development which can be applied to Duta beach tourism object.Keywords: development strategy, SWOT analysis, internal and external factors